A new multifunctional additive for blended cements. (7th November 2022) - Ferrari, Giorgio; Brocchi, Alberto; Castiglioni, Fabio; Bravo, Anna; Moretti, Emanuele; Salvioni, Davide; Squinzi, Marco; Artioli, Gilberto; Dalconi, Maria Chiara; Valentini, Luca; Dal Sasso, Gregorio
Highlights: Climate change requires a more sustainable approach of construction industry. Cement industry is developing new binders to produce concrete with a lower impact in terms of CO2 emissions. Chemical industry is asked to support this radical change by developing a newclass of Low Carbon Concrete Admixtures (LCCAs).